"All That Glitters is Gold" - Performance of Gold Exchange Traded Funds - An Empirical Analysis - Chavali, Kavita (Indian Journal of Finance, 2009)
A Gold Exchange Traded Fund (GETF) is a financial instrument like an open-ended mutual fund which mirrors the return of an index or a commodity. Its value depends on the price of gold and the price of one unit of GETF approximately reflects the price of one gram of gold. As the price of gold rises, the price of the GETF is also expected to rise by the same amount. Similarly, a fall in the price of gold will also be reflected by a drop in the price of the GETF. GETFs offer a means of participating in the gold bullion market to investors by buying and selling units on the Stock Exchanges, without physical delivery of gold. The units of GETF are purchased or sold on the stock market. GETF offers an innovative, cost-efficient and secure way to access the gold market. The process of obtaining a GETF involves a mutual fund house, which has a GETF.The mutual fund house appoints an Authorized Participant who initially buys the units of GETF from the mutual fund by exchanging actual pure gold for the units of GETF. These Authorized Participants facilitate secondary market trading through the GETF Units through the Stock Exchange, where investors can buy or sell gold units on payment, for quantities as small as one unit. The Authorized Participants (APs) are partners who ensure liquidity so that investors find ready buyers and sellers whenever they wish to transact. They also help in Market Making (providing 2-way quotes on the exchange) and educating investors of the benefits of investing. The underlying asset i.e. gold is held by a mutual fund house issuing such units either in a physical form or through a `gold receipt’ -giving right of ownership. Authorized participants can redeem the GETF Units from the mutual fund house.